The Role of TB-LAMP Method in Detecting Mycobacterium tuberculosis from Sputum of Patients Suspected of Having Pulmonary Tuberculosis - Mardiastuti H Wahid; Agus Sjahrurachman; Ardath H Sitorus; Erlina Burhan (Acta Medica Indonesiana)
Background: Indonesia is one of the countries with the highest incidence of tuberculosis (TB) in the world. Appropriate diagnosis is an effort to control TB. The World Health Organization has recommended loop-mediated isothermal amplification (LAMP). In order to be applied routinely, it is necessary to do research to evaluate the LAMP method. Methods: the research was a cross-sectional study and was carried out at the Clinical Microbiology Laboratory of the Faculty of Medicine, Universitas Indonesia, for 100 patients suspected of having pulmonary TB. Each patient handed over two direct sputum specimens. For each direct sputum specimen, an acid-fast bacilli (AFB) smear was carried out. Two direct sputum specimens from each patient were combined to produce mixed sputum. For each mixed sputum specimen, an AFB smear, Lowenstein-Jensen culture, and TB-LAMP were carried out. Results: the percentage of LAMP (+) cells in mixed sputum that was AFB (-) was 32.78%. The TB-LAMP showed a sensitivity of 100% (95% CI 89.56–100%), a specificity of 69.64% (95% CI 55.74–80.84%), positive predictive value of 71.19% (95% CI 57.73–81.86%), and negative predictive value of 100% (95% CI 88.83–100%). Conclusion: TB-LAMP has both high sensitivity and negative predictive value.